KEANEKARAGAMAN JENIS DAN PEMANFAATAN EUPHORBIACEAE DI CAGAR ALAM DUNGUS IWUL BOGOR JAWA BARAT - Ersha Farah Dea; J Jumari; Erry Wiryani; Laode Alhamd (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Euphorbiaceae is a potential plant and has a wide distribution. Nature Reserve Dungus Iwul is one area that has many different types of Euphorbiaceae plants. The purpose of this study was to determine the diversity, density and distribution as well as reviewing the use of Euphorbiaceae in Nature Reserve Dungus Iwul, Wirajaya Village, District Jasinga, Bogor, West Java. Fieldwork was conducted in May 2016. Observations were made on a sample plot with an area of 1 Ha include: the name of the species and number of individuals, DBA measurement and measurement of environmental parameters. Utilization survey conducted by interview and literature study. The results showed that the observation plots was found 17 species of Euphorbiaceae. Number of individuals based habitus were 8 individual trees, 31 individual poles, 131 saplings and 192 seedlings. Euphorbiaceae distributed by 70% in the observation plot. Euphorbiaceae used for producing animal and human feed, building materials, firewood, dyes, ornamental plants, traditional medicine and others.Keywords: Species diversity, species density, Euhphorbiaceae